Search for supersymmetry in proton-proton collisions at 13 TeV using identified top quarks - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Del,Valle AE; Flechl,M; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2018)
A search for supersymmetry is presented based on proton-proton collision events containing identifiedhadronically decaying top quarks, no leptons, and an imbalance pmissT in transverse momentum. The datawere collected with the CMS detector at the CERN LHC at a center-of-mass energy of 13 TeV, andcorrespond to an integrated luminosity of 35.9 fb−1. Search regions are defined in terms of the multiplicity ofbottom quark jet and top quark candidates, the pmissT , the scalar sum of jet transverse momenta, andthe mT2 mass variable. No statistically significant excess of events is observed relative to the expectation fromthe standard model. Lower limits on the masses of supersymmetric particles are determined at 95% confidencelevel in the context of simplified models with top quark production. For a model with direct topsquark pair production followed by the decay of each top squark to a top quark and a neutralino, top squarkmasses up to 1020 GeVand neutralino masses up to 430 GeVare excluded. For a model with pair productionof gluinos followed by the decay of each gluino to a top quark-antiquark pair and a neutralino, gluino massesup to 2040 GeV and neutralino masses up to 1150 GeV are excluded. These limits extend previous results.